THE FORMATION OF FAMILY PEDAGOGY AS A SCIENCE. - Makhmudova Muyassar Makhmudovna (International Engineering Journal For Research & Development, 2023)
This article describes in detail the formation of family pedagogy as a science and its importance in the life of every person. Family education is based on love and freedom, which are universal ideals. Harmonious personal development, carried out based on love and freedom, means that the child is in harmony with culture, nature, the people around him, and himself. The main goal of family pedagogy is to raise a child in the spirit of freedom and self-creation, to help his physical, intellectual, moral, aesthetic, and spiritual development. There is no focused goal in the family, but rather an appeal to the natural, unique child with unique interests and habits.